Static performance of non-through one-side bolted end-plate joint for floor-by-floor assembled steel structures. (February 2023) - Li, Yuan-Qi; Wu, Fu-Wei; Tan, Ming-Qing
Abstract: The static performance of non-through end-plate joint with one-side bolts for floor-by-floor assembled steel structures was investigated by means of tests and finite element simulations. A total of six monotonic static loading tests were carried out on the column-end and beam-end joints individually. The stiffness, strength characteristics and failure mechanism were obtained. A partial numerical model of the thread-fixed one-side bolted connection was established. It was proposed that the corresponding mechanical properties could be simplified to a trilinear load–displacement relationship and applied to the overall joint models. The tests and numerical simulations of the specimens were compared and analyzed. The results showed that the failure mode of the column-end joints was the tearing of the bottom welds after the yielding of cross web, while the failure modes of the beam-end joints were the failure of the threads or bolts. The influences of the thickness of cross web and flange of the column-connection, the thickness of beam end plate and the depth of threads on the failure modes and mechanical properties were studied with the test and finite element models. According to the force mechanism of the column-end and beam-end joints, the bearing capacity calculation formulae of the non-through one-side bolted end-plate joint were proposed finally.